Development of Electronic Business Management Information System At Trinita Elektro Manado Store - Alex Andaria; Hiskia K Manggopa; Mario T Parinsi (JR Education, 2022)
The purpose of the study was to determine the results of the development of an electronic business management information system and to produce a valid, practical, and efficient electronic business management management information system at the Trinita Elektro Store. The type of research used is research and development or Research and Development (R&D) using the Borg & Gall development model whose research and development steps consist of data collection and initial planning, product development (initial product), product validation, product revision. , product trial 1, product revision 2, product trial 2 and (8) final product (dissemination and implementation). The subjects in this study were business owners, technicians, cashiers, and customers at the Trinita Elektro Store. Data collection techniques using literature studies, interviews and questionnaires / questionnaires. The instruments used are expert validation sheets and product trial questionnaires. While the data analysis technique used is quantitative descriptive analysis. The results showed that the electronic business management information system was feasible to be tested after being validated by design experts and materials experts at the address https://trinitaelektro.website/. Keywords : research and development, management information system, electronic business.